Implementasi Metode Qira’ati dalam Meningkatkan Ketepatan Membaca Al-Qur’an di TPQ Manba’ul Ulum Desa Sukaraja Tahun 2022 - Fitria, Dhea; Marlina, Marlina (JUPIN (Jurnal Pendidikan Islam Nusantara), 2022)
Reading the Qur'an is considered a worship for anyone who wants to learn, appreciate, and even teach it, but it is still a problem for mankind, because there are still many children and even teachers who are still wrong in teaching and reading the Qur'an. -Qur'an. This study aims to determine: 1) the implementation of the Qira'ati method at TPQ Manba'ul Ulum Sukaraja, 2) the accuracy of reading the Qur'an of TPQ Manba'ul Ulum Sukaraja students. The research approach used is qualitative with the type of descriptive research. The results showed that the implementation of the Qira'ati method in increasing the accuracy of reading the Qur'an at TPQ Manba'ul Ulum was very effective, ustadz and ustadzah were given principles that must be adhered to in teaching the Koran, additional material taught to students in addition to learning the Koran -The students of the Koran must also memorize the reading of prayers, daily prayers, tayyibah sentences and short suras.